Isolated Metacarpal Bone Metastasis from Advanced Rectosigmoid Carcinoma - AR, Fadli; MN, Azmi; O, David; MH, Zailani (IIUM Medical Journal Malaysia, 2012)
Distant metastasis is a common sequelae of stage III colorectal adenocarcinoma. Liver and lungs are the most common sites for distant metastases, but, metastases to extremities are very rare. We report a case of rectosigmoid adenocarcinoma, which metastasizes to left first metacarpal bone, which is the first occurrence in our experience. The investigations and management of the patient are discussed.